13+3x=7x-19

Simple and best practice solution for 13+3x=7x-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+3x=7x-19 equation:


Simplifying
13 + 3x = 7x + -19

Reorder the terms:
13 + 3x = -19 + 7x

Solving
13 + 3x = -19 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
13 + 3x + -7x = -19 + 7x + -7x

Combine like terms: 3x + -7x = -4x
13 + -4x = -19 + 7x + -7x

Combine like terms: 7x + -7x = 0
13 + -4x = -19 + 0
13 + -4x = -19

Add '-13' to each side of the equation.
13 + -13 + -4x = -19 + -13

Combine like terms: 13 + -13 = 0
0 + -4x = -19 + -13
-4x = -19 + -13

Combine like terms: -19 + -13 = -32
-4x = -32

Divide each side by '-4'.
x = 8

Simplifying
x = 8

See similar equations:

| -3x+7+2x=15 | | X^2+25x=7x-81 | | 2x+2(2x+3)=66 | | 2.8=16.8 | | 3v^2+36v+49=84 | | 8+r=3r | | (-7xy^4X-2x^2y)=14x^2y^2 | | 3x^2-10xy-32y=0 | | -6p+17=3y-10 | | 11-g/2=17 | | 53.4-p=19.9 | | =-2y | | -3x-7+4x=-7 | | 6(x-.8)-.2(5x-4)=3 | | -2(z+4)=-46 | | x^2+8x-272=0 | | -1/2(x+2)+3x=-1 | | 30=-5(6n+4)+5n | | 3/4×4 | | 7r+43=1 | | 25(x+7)=9x-2 | | -3=2y+35 | | (3/7)m=6 | | X-8=2+7x-5x | | P(x)=15x-125 | | 2x+x=11+3-4x | | s+3t=-4 | | 75-u=272 | | 21x^2-76x+20=0 | | 12x+18=56-7x | | 1/5x-5/6=3/4x-5 | | 2z+x=8z-12 |

Equations solver categories